Indian traditional knowledge on defence fortification: Investigation to unravel historic subsurface changes in ancient Thanjavur (Indian Journal of Traditional Knowledge (IJTK), 2026)
Ancient Indian knowledge and wisdom on architecture and town planning, with a focus on fortification, are exemplary and evident in the ancient treatises Arthashastra and Manasara Shilpa Shastra. Thanjavur, once the capital of the Chola dynasty, is an ancient town fortified with a rampart and moat wall that houses the UNESCO-protected monument, the Brihadisvara Temple, which dates back to the 11th century. This research manuscript aims to unravel the defence planning, construction techniques, and usage of vernacular materials in the fortification of rampart and moat walls in Ancient Thanjavur town and ascertain its adherence to ancient Vedic fortification principles of Arthasastra’s Audaka or Jaladurga. Excavations undertaken for a new construction project under the Smart Cities Mission of the Government of India for Thanjavur City revealed linear composite masonry walls 50 m in length and 3 m in depth, suspected to be the side walls of the Chola era moat. At this site, soil was excavated from ground level up to 5.2 m for the proposed construction, and geotechnical investigations using standard penetration tests were conducted up to 24.2 m. The presence of a weak N value of 7 to 6 m below the excavated ground level clarified the existence of a moat that was either deposited or backfilled with soil over time, such that the rampart wall and moat walls remained submerged. This provides evidence of ancient Indian Traditional knowledge on defence planning, use of vernacular materials, and innovative construction techniques for the moat, rampart walls, and foundation during the Great Chola, Vijayanagar, and Maratha periods.